Modifying and Assessing Validity and Reliability of Motivation for Reading Questionnaire - Toni Indrayadi (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2021)
This study aimed to describe the modification process and validity and reliability assessment of instruments regarding motivations for the reading questionnaire (MRQ) for measuring reading motivation of junior high school students in Jambi, Indonesia. Eighty-three students participated in this study, selected through the respondent who returned the questionnaires. The corrected items' total correlation of SPSS 23 was applied to examine the validity and reliability of MRQ. The corrected items' total correlation of SPSS statistical analyses showed that all of the 53 modification items of MRQ were valid and reliable. It indicated that all 53 items of MRQ were appropriate for measuring the reading motivation of junior high school students in Jambi, Indonesia. It can provide a future studies screening tool for measuring the students' reading motivation.